Presence and Cybersickness in Virtual Reality Are Negatively Related: A Review - Weech, Séamas; Kenny, Sophie; Barnett-Cowan, Michael (Frontiers in Psychology, 2019)
In order to take advantage of the potential offered by the medium of virtual reality, it will be essential to develop an understanding of how to maximize the desirable experience of ‘presence’ in a virtual space (‘being there’), and how to minimize the undesirable feeling of ‘cybersickness’ (a constellation of discomfort symptoms experienced in virtual reality). Although there have been frequent reports of a possible link between the observer’s sense of presence and the experience of bodily discomfort in virtual reality, the amount of literature that discusses the nature of the relationship is limited. Recent research has underlined the possibility that these variables have shared causes, and that both factors may be manipulated with a single approach. This review paper summarizes the concepts of presence and cybersickness and highlights the strengths and gaps in our understanding about their relationship. We review studies that have measured the association between presence and cybersickness, and conclude that the balance of evidence favours a negative relationship between the two factors which is driven principally by sensory integration processes. We also discuss how system immersiveness might play a role in modulating both presence and cybersickness. However, we identify a serious absence of high-powered studies that aim to reveal the nature of this relationship. Based on this evidence we propose recommendations for future studies investigating presence, cybersickness, and other related factors.